Assessment of Rural Youth Movement from Farming to Transportation Sector in Osun State, Nigeria - Ojubanire, Michael Olukayode (2015)
The study was designed to assess the movement of rural youth from farming to the rural transportation activities; identify reasons for the movement and determined their levels of involvement in these activities. It also determined the social and economic satisfaction derived from rural transportation by the youth. This is with a view to coming up with policy strategies that could facilitate the youth participation in rural development.